PENGGUNAAN KALIMAT NOMINAL DAN VERBAL DALAM PENULISAN PARAGRAF - Lubis, Yani; Sitepu, Lunaya Khairunisya br; Putri, Izki Fidian; Zaki, Sayyid Ahmad; Putri, Sufiyani Nur Syamsiah (Yayasan Amanah Nur Aman, 2025)
This article examines the strategic role of nominal and verbal sentences in writing English paragraphs. Nominal sentences serve to introduce the topic, convey the identity, circumstances, or nature of the subject in a concise and clear manner. Meanwhile, verbal sentences are used to describe the actions, activities, or processes carried out by the subject, making the paragraphs more dynamic and informative. The balanced use of these two types of sentences can increase variety, cohesion, and coherence of paragraphs, as well as make it easier for readers to understand the content of the writing. In addition, the combination of nominal and verbal sentences also helps the writer build a logical paragraph structure, clarify the message, and prevent misunderstandings. Thus, mastery and application of nominal and verbal sentences are very important for writers, especially in the context of academic writing and scientific communication.